Energy Consumption, Energy Prices and Economic Growth: Causal Relationships Based on Error Correction Model - Osigwe, Augustine C.; Arawomo, Damilola Felix (International Journal of Energy Economics and Policy, 2015)
This study examined the Granger causality of energy consumption, oil price and economic growth in Nigeria. Two sub-categories of energy (kerosene and electricity) were equally considered. The error correction model framework was used to test the granger causality of the variables. The results for the total energy showed bidirectional causality between energy consumption and economic growth. As regards electricity, bidirectional causality was found between electricity consumption and economic growth as well as between electricity consumption and electricity price. No causal relationship exists among kerosene consumption, kerosene price and economic growth. Based on our findings, we recommend that policies that promote energy consumption and economic growth be introduced. One way of achieving this is through the adoption of appropriate energy pricing framework that takes cognisance of both the present and the future generation. Keywords: Energy consumption; Economic Growth; Kerosene Consumption; Electricity Consumption. JEL Classifications: C22; Q43; Q48